2022
DOI: 10.1111/os.13253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antibacterial Co‐Cr‐Mo‐Cu Alloys on Osteoblast Proliferation, Differentiation, and the Inhibition of Apoptosis

Abstract: Objectives To investigate the effects of antibacterial Co‐Cr‐Mo‐Cu alloys with different Cu contents on osteoblast proliferation, differentiation, and the inhibition of apoptosis to optimize the selection of surgical implantation. Methods Microstructure, phase structure, and ion release were evaluated using X‐ray diffraction, scanning electron microscopy (SEM), and inductively coupled plasma (ICP) spectrometry. The effects on osteoblast proliferation, differentiation, and apoptosis were characterized by cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Due to its transition between different oxidation states, Cu 2+ plays a role in numerous physiological processes. Duan et al 51 investigated the effect of Cu-containing alloy on osteoblast proliferation and differentiation, indicating that Cu 2+ induced the proliferation of osteoblasts at 24 to 72 h timepoints, explaining the increase of cell viability after 48 h. Furthermore, Zhang et al 52 observed that the Cu ion concentration is one of the key factors for switching the biological effects of Cu 2+ and Cu + from toxicity to activity.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its transition between different oxidation states, Cu 2+ plays a role in numerous physiological processes. Duan et al 51 investigated the effect of Cu-containing alloy on osteoblast proliferation and differentiation, indicating that Cu 2+ induced the proliferation of osteoblasts at 24 to 72 h timepoints, explaining the increase of cell viability after 48 h. Furthermore, Zhang et al 52 observed that the Cu ion concentration is one of the key factors for switching the biological effects of Cu 2+ and Cu + from toxicity to activity.…”
Section: Resultsmentioning
confidence: 99%
“…Ti6Al4V-6 wt.% Cu alloy did not negatively affect the cell viability of gingival fibroblasts and osteoblasts. It inhibited the inflammatory response of macrophages, increased the angiogenesis properties of HUVECs, and decreased local inflammatory responses by inhibiting macrophages [ 31 ]. In the present study, for 3 at.% Cu, osteoblasts proliferated comparably between days 1 and 14 for all materials.…”
Section: Discussionmentioning
confidence: 99%
“…The same results were observed in the mineralization capacity of osteoblasts without differences among materials but with a slight increase in 3 at.% Cu materials. In a previous study using the CoCrMo alloy, it was found that the addition of 2 wt.% Cu could induce osteoblast proliferation and differentiation as well as inhibit osteoblast apoptosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…%) were prepared using an investment casting method 2 wt % Induce osteoblast proliferation and differentiation and inhibit osteoblast apoptosis by generating ROS and activating mTOR signaling pathway. [ 56 ] Cu-doped 45S5 bioactive glass 0.1 wt % Enhance lipid peroxidation associated with mild growth enhancement of osteoblast-like cells. [ 57 ] Cu-doped 45S5 bioactive glass 5 wt % Induce an early osteogenic differentiation of hMSCs, promote the expression of anti-inflammatory interleukin, and reduce proinflammatory interleukin expression.…”
Section: Copper Effects On Osteoblastsmentioning
confidence: 99%
“…The addition of copper in biomaterials could promote the proliferation of osteoblasts, so as to markedly enhance the bone formation activity and accelerate the grow and repair of bone defect [ 49 , 50 , [52] , [53] , [54] , [55] ]. Duan et al [ 56 ] found the addition of Cu element in the Co–Cr–Mo alloys could stimulate ROS production in osteoblasts at a certain Cu ion concentration (2 wt%) thus promote cell proliferation. Furthermore, the addition of copper ions to the alloy resulted in decreased Adenosine 5‘-monophosphate (AMP)-activated protein kinase (AMPK) and p-AMPK level, suggesting that Cu ions could activate mammalian target of rapamycin (mTOR) signaling by downregulating AMPK phosphorylation, leading to the induction of osteoblast proliferation.…”
Section: Copper Effects On Osteoblastsmentioning
confidence: 99%